Spiking Pandemic Potential: Structural and Immunological Aspects of SARS-CoV-2. Issue 8 (August 2020) - Wang, Ying-Ting; Landeras-Bueno, Sara; Hsieh, Li-En; Terada, Yutaka; Kim, Kenneth; Ley, Klaus; Shresta, Sujan; Saphire, Erica Ollmann; Regla-Nava, Jose Angel
Abstract : SARS-Coronavirus-2 (SARS-CoV-2) causes Coronavirus disease 2019 (COVID-19), an infectious respiratory disease causing thousands of deaths and overwhelming public health systems. The international spread of SARS-CoV-2 is associated with the ease of global travel, and societal dynamics, immunologic naiveté of the host population, and muted innate immune responses. Based on these factors and the expanding geographic scale of the disease, the World Health Organization (WHO) declared the COVID-19 outbreak a pandemic–the first caused by a coronavirus. In this review, we summarize the current epidemiological status of COVID-19 and consider the virological and immunological lessons, animal models, and tools developed in response to prior SARS-CoV and MERS-CoV outbreaks that can serve as resources for development of SARS-CoV-2 therapeutics and vaccines. In particular, we discuss structural insights into the SARS-CoV-2 spike protein, a major determinant of transmissibility, and discuss key molecular aspects that will aid in understanding and fighting this new global threat. Highlights: A substantial body of scientific knowledge has been established from studies on the related SARS- and MERS-CoVs, and their respective diseases. These lessons have started to guide SARS-CoV-2 studies, therapeutics, and vaccinology. The Spike (S) protein is key to CoV infection and pathogenesis. SARS-CoV-2 S protein shows a stronger binding affinity for the host ACE2 receptor and is uniquely cleaved by furin. Some existing monoclonal antibodies against SARS-CoV S protein show cross-reactivity to SARS-CoV-2, raising their therapeutic potential against COVID-19. Immunodominant epitopes identified in SARS-CoV are highly conserved in SARS-CoV-2 and have a high potential to elicit functional T cell responses. Viral inactivation of type I interferon responses contributes to imbalanced host cytokine/chemokine responses that lead to SARS- and MERS-CoV infections and immunopathogenesis.